Creativity as the Conceptual and Pragmatic Framing of Mind - Amir Piliang, Yasraf (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2011)
As a philosophical concept, creativity is generally understood as a mental capacity of generating something new that has never existed before: ideas, compositions, arrangements, concepts, systems, forms, styles or products. As a mental capacity, it is widely believed that the end product of creativity is ‘new idea’, as an absolute creation of ‘individual genius’. This general claim about ‘newness’ as a genuine product of creativity obscures the fact that an idea can only be generated based on previous ideas, through a mechanism of ‘repetition’. The disavowal of repetition as an integral part of the concept of creativity leads to certain form of framing, namely a ‘conceptual framing’, through which newness as a relevant concept is celebrated in discourse, while the concept of repetition is concealed as irrelevant. This framing distorts the true meaning of creativity. In addition, there is another form of framing, which is more pragmatic, namely an ‘economic framing’, through which  the profit motive of creativity is exposed, whereas social, cultural, educational, and spiritual motives are concealed. Both forms of concealment have fundamentally distorted the true functions, motives and aims of  creativity. Keywords:*art, *creativity, *newness, *difference, *repetition, *borrowing, *field, *framing , *mental capacity, *social product, *capital, *power, *total expression